Fetomaternal Outcome of Pregnancy in Women with Thyroid Disease at Tertiary Care Hospital - Bashir, Nadia; Bakhsh, Fozia Muhammad; Mastoi, Saira; Reki, Nida; Achakzai, Merman; Mehwish (Indus Journal of Bioscience Research, 2025)
Background: Thyroid dysfunction is among the most common endocrine disorders in pregnancy and is associated with adverse maternal and neonatal outcomes. Objective: To determine fetomaternal outcomes of pregnancy in women with thyroid disease at a tertiary care hospital. Methodology: At the Bolan Medical College Hospital in Quetta, 250 pregnant patients with thyroid conditions aged 18 to 40 participated in a descriptive cross-sectional study. A standardized proforma was used to gather data on demographic, obstetric, and neonatal outcomes, and SPSS 26 was used for analysis. Maternal hypertension, pre-eclampsia, postpartum hemorrhage, cesarean delivery, oligohydramnios, low birth weight, and neonatal hyperbilirubinemia were among the outcomes evaluated. Thyroid illness type, parity, and maternal age were used for stratification. Results: Of the patients, 54.8% had hypothyroidism and 45.2% had hyperthyroidism. Prenatal hypertension (46%), pre-eclampsia (50%), postpartum hemorrhage (52.4%), LSCS (48.4%), oligohydramnios (46%), low birth weight (47.6%), and neonatal hyperbilirubinemia (42.4%) were among the high rates of unfavorable outcomes that were noted. Although there were indications toward a higher risk of low birth weight in older moms, stratified analysis revealed no significant correlation between age, parity, or thyroid type with major outcomes. Conclusion: Thyroid disorders during pregnancy substantially increase maternal and neonatal morbidity. Early screening, timely treatment, and close monitoring are crucial to improve outcomes.